Adult-onset Renal Neuroblastoma: Case Report and Literature Review - Yao-Ren Yang; Cih-En Huang (Journal of Cancer Research and Practice)
Neuroblastoma is an extremely rare neoplasm in adults, with a poorer prognosis compared to pediatric neuroblastoma. Due to its rarity, there are no specific treatment guidelines for adult neuroblastoma. Here, we report a case of adult renal neuroblastoma presenting initially with painless and gross hematuria. Enhanced computed tomography revealed an infiltrative, heterogeneously enhanced renal mass at the lower pole of the right kidney, accompanied by regional lymphadenopathies. The initial impression was renal cell carcinoma, and a right nephroureterectomy with regional lymph node dissection was performed. Pathologic examination confirmed the diagnosis of primary renal neuroblastoma with a differentiating subtype. The patient was classified as having International Neuroblastoma Staging System stage 2B or International Neuroblastoma Risk Group Staging System stage L2. The patient underwent six courses of adjuvant chemotherapy, and no disease recurrence was observed during a 7-year follow-up period.